PERENCANAAN KOLAM PELABUHAN PONDOK DAYUNG FASHARKAN TANJUNG PRIOK JAKARTA UTARA - Agus Ristiyanto; Asif Murtadlo; Salamun Salamun; Hari Budieny (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Ports of Pondok Dayung is one of the special port designation refers to as one of the supporting facilities and infrastructure facilities NKRI defense, such as privatization TNI navy military has its have means to sea port don't depend on other agencies. Planning a pool port of Pondok Dayung Fasharkan design covering breakwaters, design port dock, grooves cruise design, as well as design lap pool port. Functionally, this port will be used as a berthing dock and military vessels, as well as a repair ships for the Navy in particular regional western Indonesia and the surrounding region. Planning begins with the data include wind speed data processing for generation forecasting waves in the sea area. The result shows the significant wave height (Ho = 1.53 m) and significant wave period (To = 9.585 sec) to reset wave when the plan for 50 years. Data processing tidal sea water as well as map data is used as reference planning bathimetry high elevation breakwater and dock buildings, from the calculation of the value obtained tidal sea level plan HHWL = + 51.4 cm, MSL = ± 0.0 cm, and LLWL = -34.6 cm. The data is used as reference fleet planning calculations obtained wide shipping channel groove width 216 m (two lines), and the great depth of the draft plan of the port pool D = ± 12.25 m from the sea bet. Geotek the data used to determine the characteristics of the soil used as reference planning building type breakwater, pier foundation and structure planning. Planning generated breakwater building type hypotenuse (1: 1.5) with a total length of 1292 m, the number of tier 2 Secondary layer 1 m thick layer of heavy stones to 168-200 kg layer Core layer in grain weight 16-20 kg, and design mercu elevation ± 3.79 m of MSL. Plan a total of 252 m long quay with a plan elevation of +1.07 m MSL, plan structure 20 cm thick floor slabs, pile foundation structure Spun Pile Ø 50 cm with concrete quality K 500. dock Fender ie type V (400H 1000L) the impact energy capacity of 160 kN, as well as the type fastening Bollard pull capacity of 35 tons.